Analisis Kepuasan Mahasiswa terhadap Pembelajaran Daring di STIKes Baiturrahim Jambi - Fithriyani Fithriyani; Rino M (Universitas Baiturrahim, 2022)
Distance learning is an alternative to learning in the COVID-19 pandemic era, one of which is by utilizing various learning applications where the educator factor, namely the lecturer, plays a major role. Lecturers must have special skills and abilities, including pedagogical competence, professional competence, personality competence and social competence. The learning carried out by lecturers is like the services provided to consumers or students. In providing services, of course, what must be considered is the quality of the service itself. The high and low quality of service can only be seen by students. When the quality of service exceeds the expectations thought by students, there will be a sense of satisfaction. The description of student satisfaction related to online learning performance by lecturers is very satisfying for all indicators of personality and social competence. The purpose of this study was to describe student satisfaction with online learning at Baiturahim College of Health Sciences. This research is a survey type research with a quantitative approach. The analysis in this study uses descriptive analysis method. The respondents of this study were students of the nursing science study program who took online lectures, namely 81 people which were held from October 2021 to February 2022. The results of the study were obtained. Most (56.8%) were not satisfied with online learning at STIKes Baiturahim. Suggestions for the STIkes Baiturahim Institution to increase the use of information technology in learning methods, especially online, by adjusting the development of information media.